Response costs of mammography adherence: Iranian women’sperceptions - Mahsa Khodayarian; Seyed Saied Mazloomi-Mahmoodabad; Minoor Lamyian; Mohammad Ali Morowatisharifabad; Hossein Tavangar (Health Promotion Perspectives, 2016)
Background: Mammography as the most common secondary prevention method has known to be helpful in detecting breast cancer at the early stages. Low level of participation among women toward mammography uptake due to cultural beliefs is a great concern. This study aimed at exploring the perceptions of women about response costs of mammography adherence(MA) in Yazd, Iran. Methods: A qualitative study using semi-structured interviews was performed. Fourteen women,one oncology nurse, and a breast cancer survivor were purposefully interviewed. Interviews were transcribed verbatim and analyzed by directed content analysis method based on protection motivation theory (PMT). Results: One main theme was emerged from the analysis namely called "response costs".Two main categories were also emerged from the data; (1) psychological barriers with six subcategories including "embarrassment," "worry about being diagnosed with cancer,""preoccupation with underlying disease," "misconception about mammography," "need for an accompanying person," and "internalizing the experiences of the others," and (2) maladaptive coping modes which encompassed three subcategories: "religious faith," "fatalism," and"avoidance and denial." Conclusion: Useful information was provided about the response costs of mammography utilization based on the perceptions of women. Cognitive barriers may be decreased by conducting modifications in women’s awareness and attitude toward MA as well as changing the national health system infrastructures. Incorporating religious and cultural belief systems into MA educational programs through motivational messages is recommended.